PENGARUH STIGMA LULUSAN PENDIDIKAN KESETARAAN TERHADAP KEPUTUSAN REKRUTMEN DI DUNIA KERJA - Bayu Adi Laksono; Ahmad Hamdan; Muhammad Rafli Alviansyah (IKIP Siliwangi, 2023)
The purpose of this study was to determine the stigma of Equality Education graduates from the employer's point of view and its impact on their decision to accept prospective workers from Equality Education graduates. Equality education is known as a flexible education system that is not limited by age, time, or learning methods. The flexibility of the learning system is considered by the community that equality education is a place to get a diploma with the easy way. On the other hand, in the world of work, competencies are needed that must be possessed by job applicants. One of these competencies is generated from the learning process in the scope of formal and non-formal education. Employers in deciding to accept a worker certainly have considerations, one of which is of course the stigma that is formed in society. This research method uses a quantitative approach with a survey method involving 100 employers (HRD/Personnel/Business Owners) in Tasikmalaya City. Collecting data using a questionnaire and deepened by interviews. Data analysis with descriptive approach and simple linear regression analysis using statistical software version 23.0 for windows. The results showed that the stigma of equality education graduates had a positive but not significant effect on job acceptance decisions.